2021
DOI: 10.1525/elementa.2020.00143
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing detection probabilities of advanced mobile leak surveys

Abstract: Advanced leak detection (ALD) to survey local natural gas distribution systems has reached a point in technological maturity where new federal regulations will require its use in compliance surveys. Because most of these deployments are conducted by commercial providers, there has been little publicly available data documenting characteristics of the underlying methane (CH4) plumes that are the core features measured in ALD surveys. Here, we document key features of CH4 plumes measured in ALD surveys of 15 U.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…As an additional caveat for the data collected in our 12 cities, some of the high emission rate estimates might be the result of poor sampling statistics for these locations, as a consequence of the strategy of short-term wide-area surveys with infrequent revisits (e.g., Munich, DE, and Birmingham, UK), which can lead to an overall overestimate in the emission rate . We note that cities that have been surveyed more completely and frequently (e.g., Toronto, CA, and London, UK) should be less susceptible to these high biases, because unusually high local methane enhancements that can lead to very high emission rate estimates will average out when combined with data from multiple survey days.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…As an additional caveat for the data collected in our 12 cities, some of the high emission rate estimates might be the result of poor sampling statistics for these locations, as a consequence of the strategy of short-term wide-area surveys with infrequent revisits (e.g., Munich, DE, and Birmingham, UK), which can lead to an overall overestimate in the emission rate . We note that cities that have been surveyed more completely and frequently (e.g., Toronto, CA, and London, UK) should be less susceptible to these high biases, because unusually high local methane enhancements that can lead to very high emission rate estimates will average out when combined with data from multiple survey days.…”
Section: Resultsmentioning
confidence: 95%
“…A disadvantage of this approach is that many streets were surveyed only once or twice. Controlled release experiments , and frequent passages of the same leak location have shown that emission estimates from a single detected source can vary by more than an order of magnitude between individual passages and that emission rate estimates based on infrequent visits are biased high. A simple explanation for changing local enhancements is changes in wind speed and direction.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, mobile measurement methods using vehicles with fast and high-precision laser instrumentation have been established for leak detection and emission quantification in numerous cities (Jackson et al, 2014;von Fischer et al, 2017;Weller et al, 2018;Keyes et al, 2020;Ars et al, 2020;Maazallahi et al, 2020b;Defratyka et al, 2021;Luetschwager et al, 2021;Fernandez et al, 2022). In situ measurements of atmospheric CH 4 from mobile vehicles are used to pinpoint and quantify CH 4 emission sources at street level in urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…We explore variations in the frequency of leak indications derived from our previous urban methane surveys, where we used high-sensitivity methane analyzers deployed in Google Street View cars . The technological approach for gathering this leak indication data, now commonly known as advanced leak detection (ALD) , has been identified as a best practice for finding natural gas leaks and estimating their size . Our survey data included atmospheric methane concentrations in 13 U.S. metro areas, covering neighborhoods that are home to 4.5 million people.…”
Section: Introductionmentioning
confidence: 99%